Pengaruh Dividend Yield, DPR, EPS, ROE Dan SIZE Terhadap Harga Saham (Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - Prakoso, Ricky Eko; , Drs. Sri Padmantyo, MBA (2016)
This research target is to know the Dividend Yield have an effect on to share price. To know the Dividend Payout Ratio have an effect on to share price. To know the Earning per Share have an effect on to share price. To know the Return on Equity have an effect on to share price. To know the Size have an effect on to share price. Method election sample use the purposive sampling while sample used in this research manufacturing business enlisted in BEI and the following intake sample criterion : Company manufacturing sector enlisted in Effect Exchange Indonesia year 2012-2014. Publishing financial statement for the period of ending the date 31 December 2012, 2013, 2014 and own the pregnant complete data all element or element financial statement needed in research. Pursuant to this research result known the Dividend Yield have the influence which significant to share price. Dividend Payout Ratio have the influence which significant to share price. Earning per Share have the influence which significant to share price. Return on Equity have the influence which significant to share price. Size haven't the influence which significant to share price.